Carbon/epoxy composite foot structure for biped robots. (15th April 2016) - Lee, Jinyi; Lee, Dongyoung; Park, Jongwon; Choi, Ilbeom; Lim, Jun Woo; Kim, Soohyun; Lee, Dai Gil
Abstract: Although aluminum structures are generally used for robot structures due to their high specific strength, aluminum feet for fast running biped robots are vulnerable to fatigue failure due to the low fatigue limit and low vibration damping of aluminum structures under repeated impact loadings on the feet. On the other hand, carbon/epoxy composites not only have a much higher specific fatigue limit but also have a higher material damping than that of aluminum. In this study, a carbon/epoxy composite foot structure of a biped robot was developed. The composite foot structure was designed for optimum performances such as weight saving, natural frequency, damping, and compliance for vibration isolation. Then its performances were analytically and experimentally obtained and compared with those of an aluminum foot structure. Finally, an optimum configuration of the composite foot structure was suggested for the reliable dynamic performance of the biped robot.